PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI DALAM PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) PADA KELAS V DI UPT SDN 35 AMBACANG KAMBA KABUPATEN PESISIR SELATAN - Gema Ari Yono; Hidayati Azkiya (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This research was motivated by the lack of explanatory text writing skills for class V students at UPT SDN 35 Ambacang Kamba, Pesisir Selatan Regency. This is due to the lack of teacher variation in using learning methods in the learning process. The aim of this research is to improve explanatory text writing skills using the Student Teams Achievement Division (STAD) model for class V SDN 35 Ambacang Kamba. The theory used in this research is the STAD model proposed by Wulandari (2022:20). This type of research is Classroom Action Research (PTK) which includes 4 stages, namely planning, implementation, observation and reflection. The number of students is 18 people. The research instruments used were teacher and student activity observation sheets, explanatory text writing skills activities. This research was carried out in two cycles, each cycle consisting of two meetings with a final test. The subjects of this research were class V at UPT SDN 35 Ambacang Kamba, Pesisir Selatan Regency. The research instruments used were explanatory text writing skills sheets, teacher activity sheets, student activity sheets. The results of the research showed that the average percentage of implementation of teacher activities in cycle I reached 68.31% in the sufficient category and in cycle II it reached 89.81% in the very good category. The average percentage of implementation of student activity data in cycle I reached 69.53% in the sufficient category and in cycle II it reached 86.62% in the very good category. Completion of students' explanatory text writing skills in cycle I was 44.44% with an average of 64.72 and increased in Cycle II by 83.33% with an average of 81.27 with an average increase of 38.89. From the research results, it can be concluded that learning Indonesian in students' explanatory text writing skills using the STAD learning model can improve the explanatory text writing skills of class V students at UPT SDN 35 Ambacang Kamba, Pesisir Selatan Regency.